(untitled) (Siddhajyoti Interdisciplinary Journal, 2026)
Student teachers (STs) are scholars who are in the process of becoming certified teachers. They plan for and complete a required teaching practice (TP) as part of their university course within a period of time in simulated and real classrooms under the supervision of mentor teachers. This article examines STs’ perception of on-campus and off-campus activities in TP. Using a quantitative survey research design, data were collected from 80 randomly selected STs (out of 100), who were assigned to 30 cooperative schools across the Surkhet district from Surkhet Multiple Campus, Tribhuvan University. A structured questionnaire was administered to collect the insights of STs about TP in-campus preparation and off-campus teaching experiences. Through descriptive statistical analysis of the data, the findings revealed that STs generally performed well during both on-campus and off-campus teaching practices, demonstrating effective engagement in lesson planning, assessment, and classroom instruction. However, they faced challenges related to peer observation, consistency of supervision, and preparation for assessments. Moreover, the study highlighted that structured feedback mechanisms, such as teaching workshops and encouragement of self-reflection, are essential to enhance the teaching performance of STs. The study recommends that the Department of Teaching Practice (DTP) identify and implement robust supervision mechanisms to promote STs’ experiential reflective learning of professional skills, which improves the overall quality of teacher education programs.